Myeloperoxidase-Derived 2-Chlorohexadecanal Is Generated in Mouse Heart during Endotoxemia and Induces Modification of Distinct Cardiomyocyte Protein Subsets In Vitro - Prasch, Jürgen (Int J Mol Sci, 2020)
Sepsis is a major cause of mortality in critically ill patients and associated with cardiac dysfunction, a complication linked to immunological and metabolic aberrations. Cardiac neutrophil infiltration and subsequent release of myeloperoxidase (MPO) leads to the formation of the oxidant hypochlorous acid (HOCl) that is able to chemically modify plasmalogens (ether-phospholipids) abundantly present in the heart. This reaction gives rise to the formation of reactive lipid species including aldehydes and chlorinated fatty acids. During the present study, we tested whether endotoxemia increases MPO-dependent lipid oxidation/modification in the mouse heart. In hearts of lipopolysaccharide-injected mice, we observed significantly higher infiltration of MPO-positive cells, increased fatty acid content, and formation of 2-chlorohexadecanal (2-ClHDA), an MPO-derived plasmalogen modification product. Using murine HL-1 cardiomyocytes as in vitro model, we show that exogenously added HOCl attacks the cellular plasmalogen pool and gives rise to the formation of 2-ClHDA. Addition of 2-ClHDA to HL-1 cardiomyocytes resulted in conversion to 2-chlorohexadecanoic acid and 2-chlorohexadecanol, indicating fatty aldehyde dehydrogenase-mediated redox metabolism. However, a recovery of only 40% indicated the formation of non-extractable (protein) adducts. To identify protein targets, we used a clickable alkynyl analog, 2-chlorohexadec-15-yn-1-al (2-ClHDyA). After Huisgen 1,3-dipolar cycloaddition of 5-tetramethylrhodamine azide (N(3)-TAMRA) and two dimensional-gel electrophoresis (2D-GE), we were able to identify 51 proteins that form adducts with 2-ClHDyA. Gene ontology enrichment analyses revealed an overrepresentation of heat shock and chaperone, energy metabolism, and cytoskeletal proteins as major targets. Our observations in a murine endotoxemia model demonstrate formation of HOCl-modified lipids in the heart, while pathway analysis in vitro revealed that the chlorinated aldehyde targets specific protein subsets, which are central to cardiac function.